2008
DOI: 10.1158/0008-5472.can-07-5870
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomics IdentifiesRAB23as an Invasion Mediator Gene in Diffuse-Type Gastric Cancer

Abstract: Recurrent genomic amplifications and deletions are frequently observed in primary gastric cancers (GC). However, identifying specific oncogenes and tumor suppressor genes within these regions can be challenging, as they often cover tens to hundreds of genes. Here, we combined high-resolution array-based comparative genomic hybridization (aCGH) with gene expression profiling to target genes within focal high-level amplifications in GC cell lines, and identified RAB23 as an amplified and overexpressed Chr 6p11p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 47 publications
2
73
0
Order By: Relevance
“…Endosomes play key roles in the control of cell signaling, the epithelial to mesenchymal transition, and cell adhesion and migration, thus influencing cancer development (Lanzetti and Di Fiore, 2008). Several studies have demonstrated that members of the RAB family are up-regulated in GC tissues (Hou et al, 2008;Cao et al, 2013). SOX4 is a member of the SRYrelated HMG-box (SOX) family of transcription factors involved in cell apoptosis as well as tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Endosomes play key roles in the control of cell signaling, the epithelial to mesenchymal transition, and cell adhesion and migration, thus influencing cancer development (Lanzetti and Di Fiore, 2008). Several studies have demonstrated that members of the RAB family are up-regulated in GC tissues (Hou et al, 2008;Cao et al, 2013). SOX4 is a member of the SRYrelated HMG-box (SOX) family of transcription factors involved in cell apoptosis as well as tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other than the Rabs described above, other Rabs, such as Rab23, have also been linked to cancer cell migration and invasion [Hou et al, 2008]. In this case, however, the underlying mechanism is unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Rab23 is overexpressed in bladder, 73 gastric 74 and ovarian carcinoma 75 while it is purported to be downregulated in triple negative breast cancer. 76,77 Similarly Rab25 has differing expression levels with increased expression in estrogen and progesterone receptor positive breast cancer, 78 and suppression in colon and head and neck tumors.…”
Section: Differential Expression Of Rab Gtpases In Cancer Cellsmentioning
confidence: 99%
“…77 However, Rab25 is also said to be an oncogene given its role in advanced stages of ovarian and breast cancers and is linked to an increase in malignancy and migration of the epithelial cells by modulating cell proliferation (both anchorage dependent and independent cells), trafficking of integrin and suppressing apoptosis. 75 Specifically, Rab25 promotes cell survival by increasing PI3-Kinase signaling through the interaction with the Rab-coupling protein, which in turn sustains the recycling of both EGFR and the fibronectin receptor (integrin a5b1). It was determined that Rab25 accelerates cell migration by actively moderating the recycling of integrins via the chloride intracellular channel protein 3 where this process is required in the freeing of the cell rear in cell migration and invasion.…”
Section: 93mentioning
confidence: 99%
See 1 more Smart Citation